Effect Of Arbuscular Mycorrhizal Fungi For Their Symbiotic Efficiency On Two Varieties Of Solanum Lycopersicum L. - PUSHPA. K.KAVATAGI; H.C.LAKSHMAN (International Journal of Pharma and Bio Sciences, 2012)
Earthen pot experiments were conducted in a randomized block design with three replications to evaluate the effects of Tomato (Solanum lycopersicum L.) varieties, PMK-1 and Vaibhav. The indigenous species; Glomus fasciculatum (Thaxter) Gerdmann and Trappe emend. Walker & Koske, Gigaspora margarita Becker & Koske, Sclerocystis dussii (Patouillard) von Hohnel, and Acaulospora laevis Gerd & Trappe., were used in the study species Sorghum was used as a trap host. All species had the ability to colonize tomato root with different colonization levels. Significantly higher root were colonized by Glomus fasciculatum compared to Acaulospora laevis. A Glomus fasciculatum significantly increased shoot length, root length, dry and fresh weight of shoot and root, number of fruits and flowers. Higher spores were counted in Glomus fasciculatum inoculated plant compared to Gigaspora margarita, Sclerocystis dussii and Acaulospora laevis plants. The relationship between mycorrhiza and plant is very widely spread among terrestrial vascular plants. Inoculation with arbuscular mycorrhizal fungi (AMF) were significantly enhanced tomato shoots and root biomass. The endogenous species, Glomus fasciculatum was the best species among four species tested.